THE ROLE OF THE SERVICE SECTOR IN THE DEVELOPMENT OF THE COUNTRY (American Journal of Business Management, Economics and Banking, 2023)
The content and essence of the service sector in the article and the socio-economic significance of its rapid development, employment of the population in the service sectors an analysis of their structural structures is presented. A comparative analysis of certain data with the regions of Uzbekistan and Samarkand was made.